Silybin suppresses ovarian cancer cell proliferation by inhibiting isocitrate dehydrogenase 1 activity. Issue 9 (21st July 2022) - Wei, Zibo; Ye, Shuangyan; Feng, Haipeng; Zeng, Chong; Dong, Xinhuai; Zeng, Xiaokang; Zeng, Liming; Lin, Xu; Liu, Qiuzhen; Yao, Jie
Abstract: Metabolic reprogramming is a sign of malignant tumors, and targeting the metabolism of tumor cells has become a promising therapeutic approach. Here, we report that Silybin (a nontoxic flavonoid commonly used for liver protection) exhibits prominent anti‐tumor effects on human ovarian cancer cells. Treatment of an ovarian cancer cell line with Silybin interfered with glutamine metabolism and the tricarboxylic acid cycle. We applied the drug affinity responsive target stability approach to show that Silybin binds to isocitrate dehydrogenase 1 (IDH1). This combination leads to reduced phosphorylation of IDH1 and inhibits enzyme activity. IDH1 dysfunction significantly increases the ratio of NADP/NADPH in the cell, causing an increase in reactive oxygen species generation. Immunohistochemistry demonstrated that IDH1 was increased in ovarian cancer samples compared with normal para‐tumoral tissues. Xenograft murine experiments indicated that Silybin administered orally suppressed the growth of the tumor formed by ovarian cancer cells. In combination, our data strongly suggest that Silybin targets IDH1 in ovarian cancer cells and may be a novel treatment candidate. Abstract : Here, we report that the Silybin exhibits prominent anti‐tumor effects on human ovarian cancer cells. Treatment of an ovarian cancer cell line with Silybin interfered with glutamine metabolism and the tricarboxylic acid cycle. In combination, our data strongly suggest Silybin targets IDH1 in ovarian cancer cells and it may provide a novel treatment candidate.